Fussy eating in toddlers: A content analysis of parents' online support seeking. Issue 3 (19th March 2021) - Fraser, Kylie; Markides, Brittany Reese; Barrett, Norma; Laws, Rachel
Abstract: The development of healthy eating habits in childhood is essential to reducing later risk of obesity. However, many parents manage fussy eating in toddlerhood with ineffective feeding practices that limit children's dietary variety and reinforce obesogenic eating behaviours. Understanding parents' feeding concerns and support needs may assist in the development of feeding interventions designed to support parents' uptake of responsive feeding practices. A total of 130 original posts by parents of toddlers (12–36 months) were extracted from the online website Reddit's 'r/Toddlers' community discussion forum over a 12‐month period. Qualitative content analysis was used to categorise the fussy eating topics that parents were most concerned about and the types of support they were seeking from online peers. The most frequently raised fussy eating concerns were refusal to eat foods offered, inadequate intake (quantity and quality), problematic mealtime behaviours and changes in eating patterns. Parents were primarily seeking practical support (69.2%) to manage emergent fussy eating behaviours. This consisted of requests for practical feeding advice and strategies or meal ideas. Nearly half of parents sought emotional support (47.7%) to normalise their child's eating behaviour and seek reassurance from people with lived experience. Informational support about feeding was sought to a lesser extent (16.2%). Fussy eating poses a barrier to children's dietary variety and establishing healthy eating habits. These results suggest parents require greater knowledge and skills on 'how to feed' children and support to manage feeding expectations. Health professionals and child feeding interventions should focus on providing parents with practical feeding strategies to manage fussy eating. Supporting parents to adopt and maintain responsive feeding practices is vital to developing healthy eating habits during toddlerhood that will continue throughout adulthood.